2010
DOI: 10.1002/jnr.22458
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐talk between STAT1 and PI3K/AKT signaling in HIV‐1‐induced blood–brain barrier dysfunction: Role of CCR5 and implications for viral neuropathogenesis

Abstract: How neuroinflammation affects signaling pathways leading to human blood–brain barrier (BBB) dysfunction during HIV-1 infection is incompletely understood. We previously demonstrated that signal transducers and activators of transcription-1 (STAT1) signaling is involved in HIV-1 induced BBB damage and is relevant to viral neuropathogenesis. The objective of this study was to delineate the signaling pathways upstream and downstream of STAT1 involved in HIV-1-induced endothelial dysfunction. We show that HIV-1 ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 38 publications
1
26
0
Order By: Relevance
“…One downstream consequence of TGFβ1 is the activation of phosphatidylinositol-3 kinase/Akt pathway signaling(42), which has been demonstrated to promote vascular permeability in cancer models(43, 44). Also, this pathway has been shown to induce BBB permeability following focal cerebral ischemia(45), HIV-induced BBB disruption(46), and traumatic brain injury(47). In addition to this, we have previously identified that inhibition of TGFβ1 can lead to increased expression of the hedgehog transcription factor Gli1(16).…”
Section: Discussionmentioning
confidence: 99%
“…One downstream consequence of TGFβ1 is the activation of phosphatidylinositol-3 kinase/Akt pathway signaling(42), which has been demonstrated to promote vascular permeability in cancer models(43, 44). Also, this pathway has been shown to induce BBB permeability following focal cerebral ischemia(45), HIV-induced BBB disruption(46), and traumatic brain injury(47). In addition to this, we have previously identified that inhibition of TGFβ1 can lead to increased expression of the hedgehog transcription factor Gli1(16).…”
Section: Discussionmentioning
confidence: 99%
“…Microglial- mediated cell death also appears to involve JAK/STAT3 and NF-κB [62]. In addition, JAK/STAT signaling has been shown to promote and modulate inflammatory processes [62], [63] leading to human BBB dysfunction in HIV infection [64], the latter dysfunction was mediated through CCR5 receptor which is involved in HIV-1 binding to HBVEC and activating the phosphoinositide-dependent kinase-1 (PDK1) and the serine-threonine protein kinase AKT [64]. Furthermore, some studies have shown that JAK2-STAT3 activation plays a role in post-ischemic brain neuronal damage [54] and liver cell inflammation and apoptosis [65], [66].…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular signaling by chemokine receptors is dependent on neighboring G-proteins. Several signaling molecules related to the activation of chemokine receptors have been identified, including Akt/PKB, ERK1/2, mitogen-activated protein kinase, PI3K, STAT1, and NF-κB [20,29,50]. However, little is known about the downstream signaling pathways regulated by CCL5-CCR5 interaction in glioma.…”
Section: Discussionmentioning
confidence: 99%